Frequency of tail loss reflects variation in predation levels, predator efficiency, and the behaviour of three populations of brown anoles - Bateman, Bill; Fleming, P. (Wiley-Blackwell Publishing Ltd, 2011)
We investigated two predictions regarding the incidence of tail regeneration in lizards for three populations ofbrown anoles exposed to varying predation levels from the same predator (cats). Firstly although inefficientpredators are likely to increase the incidence of regenerated tails (i.e. lizards can escape through tail autotomy),highly efficient predators will kill and eat the lizard and thus leave no evidence of autotomy. At the site with nocats, only 4% of anoles demonstrated signs of tail regeneration. This value was not significantly different from thesite where feral cats (i.e. ‘efficient’ predators that would capture prey to eat, as supported by behaviouralobservation) were present (7%). By contrast, 25% of anoles present at the site with pet cats (well-fed domesticatedcats that caught and played with anoles, i.e. were ‘inefficient’ predators) exhibited regenerated tails. Secondly, moreobvious lizards are more susceptible to predation attempts. Supporting this hypothesis, our data indicate a higherincidence of regenerated tails (28%) was recorded amongst adult males (which are territorial, occupying exposedpositions) compared to females and subadult males (17%) or juveniles (1%). In conclusion, the behaviour of boththe predator and the lizard influences the frequency of regenerated tails in brown anoles.